Preliminary screening of Alpha-1 Antitrypsin (A1AT) Phenotype among Healthy Kelantanese - Wan Azman, Wan Norlina; Mohammad Nazri, Nor Amirah; Tuan Ismail, Tuan Salwani; Harun, Azian; Yaacob, Najib Majdi; Sulong, Sarina; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Che Mat, Mahaya; Zulkeflee, Hani Ajrina; Musa, Norsyuhadah (Faculty of Medicine Universiti Kebangsaan Malaysia, 2023)
Introduction: Alpha-1 antitrypsin deficiency is a hereditary condition resulting from a SERPINA1 gene mutation that increases susceptibility to emphysema and cirrhosis, thus prompting efforts for early screening. The standard allele is “M,” while the allelic variants most frequently linked to pathological conditions are “Z” and “S.” Materials and Methods: A cross-sectional study was conducted among adults aged 18 to 80 who voluntarily participated between January 2021 and January 2022. A total of 94 healthy control Kelantanese were recruited. Participants with a history of acute or chronic infection, autoimmune disease, or immunocompromised were excluded. AIAT phenotype determination was performed using agarose gel isoelectrofocusing (IEF) SEBIA. Statistical analysis was carried out with SPSS version 27. Results: The study participants with a mean age of 36.7 (SD+7.7). The most prevalent AIAT phenotype among Kelantanese was PiMM, 94% (n=88) and the PiMX phenotype, 6% (n=6). Other phenotypes such as MS, MZ, S and Z were undetected. Conclusion: The findings of this study suggest that the PiMM phenotype exhibits the highest prevalence among the Kelantan population. In contrast, the PiMX phenotype is observed in a relatively small yet significant proportion of people. While AIAT deficiency is under-recognised, its occurrence varies among various populations. Therefore, the use of early screening measures has the potential to impede the advancement of underlying pulmonary conditions and mitigate the occurrence of secondary consequences associated with hepatic diseases.